Evaluation of prehospital undertriage in relation to trauma team activation: results from a prospective study in 12 level one German trauma centers - Düsing, Helena; Hagebusch, Paul; Baacke, Markus; Bieler, Dan; Caspers, Michael; Clemens, Valentin; Fröhlich, Matthias; Hackenberg, Lisa; Hartensuer, Renè; Imach, Sebastian; Jensen, Kai Oliver; Keß, Annette; et al. (Journal of Clinical Medicine, 2024)
Background/Objective: This prospective, multicenter observational cohort study was carried out in 12 trauma centers in Germany and Switzerland. Its purpose was to evaluate the rate of undertriage, as well as potential consequences, and relate these with different Trauma Team Activation Protocols (TTA-Protocols), as this has not been done before in Germany. Methods: Each trauma center collected the data during a three-month period between December 2019 and February 2021. All 12 participating hospitals are certified as supra-regional trauma centers. Here, we report a subgroup analysis of undertriaged patients. Those included in the study were all consecutive adult patients (age ≥ 18 years) with acute trauma admitted to the emergency department of one of the participating hospitals by the prehospital emergency medical service (EMS) within 6 h after trauma. The data contained information on age, sex, trauma mechanism, pre- and in-hospital physiology, emergency interventions, emergency surgical interventions, intensive care unit (ICU) stay, and death within 48 h. Trauma team activation (TTA) was initiated by the emergency medical services. This should follow the national guidelines for severe trauma using established field triage criteria. We used various denominators, such as ISS, and criteria for the appropriateness of TTA to evaluate the undertriage in four groups. Results: This study included a total of 3754 patients. The average injury severity score was 5.1 points, and 7.0% of cases (n = 261) presented with an injury severity score (ISS) of 16+. TTA was initiated for a total of 974 (26%) patients. In group 1, we evaluated how successful the actual practice in the EMS was in identifying patients with ISS 16+. The undertriage rate was 15.3%, but mortality was lower in the undertriage cohort compared to those with a TTA (5% vs. 10%). In group 2, we evaluated the actual practice of EMS in terms of identifying patients meeting the appropriateness of TTA criteria; this showed a higher undertriage rate of 35.9%, but as seen in group 1, the mortality was lower (5.9% vs. 3.3%). In group 3, we showed that, if the EMS were to strictly follow guideline criteria, the rate of undertriage would be even higher (26.2%) regarding ISS 16+. Using the appropriateness of TTA criteria to define the gold standard for TTA (group 4), 764 cases (20.4%) fulfilled at least one condition for retrospective definition of TTA requirement. Conclusions: Regarding ISS 16+, the rate of undertriage in actual practice was 15.3%, but those patients did not have a higher mortality.